Paradoks Omnibus Law Kesehatan: Hegemoni Negara dan Erosi Otonomi Profesi Medis di Indonesia - Hertanto, Yudhi; Ady Purwoto (Universitas Pancasakti Tegal, 2026)
The enactment of Law Number 17 of 2023 concerning Health through the omnibus law method marks a fundamental transformation in Indonesia's health legal system. This research aims to analyze the legal politics of the formation of the Health Law, focusing on the dialectic between fulfilling public interests and protecting medical professionalism. This research constitutes normative legal research (yuridis normatif) employing three approaches: the statute approach, conceptual approach, and philosophical approach. The data sources are secondary, encompassing academic manuscripts, parliamentary minutes, Constitutional Court Decision Number 182/PUU-XXII/2024, relevant legislation, and scholarly literature. Data collection techniques were conducted through library research with systematic tracing of legal documents and academic literature. Data analysis was performed descriptively-analytically using deductive methods to draw systematic and comprehensive conclusions. The findings demonstrate that philosophically, the Health Law represents a manifestation of state responsibility within the welfare state framework, shifting the health paradigm from a cost burden to social investment. Sociologically, this legislation responds to the crisis in medical personnel distribution and digital disruption, although facing resistance from professional organizations due to the erosion of professional autonomy. Juridically, the omnibus law method aims to simplify hyper-regulation; however, Constitutional Court Decision Number 182/PUU-XXII/2024 affirms the necessity of institutional independence for the council and collegium to preserve professional dignity. This research concludes that harmonization between state control and professional independence constitutes the key to the effectiveness of the national health system. This research recommends strengthening the operational and financial independence of the Health Council and Collegium, transparent implementation of the Health Sector Master Plan, and optimization of restorative justice mechanisms in medical dispute resolution.